2001
DOI: 10.1023/a:1004810120032
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The public mental hospital system was created in part because many mentally ill people were being held in prisons and jails. Support for those hospitals waned over time, however, and by the time they had degenerated into "snake pits" a consensus was reached to close them down. Unfortunately, they were not replaced with adequate community mental health resources, so as the hospitals have emptied, the prisons and jails have filled, partly with the mentally ill. That is the destructive reason for the growth of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Due to the large-scale closure of psychiatric hospitals, the federal war on drugs campaign, and communities with limited resources, the criminal justice system has become the default caregiver for a large number of persons with SMI, as there are now more people with SMI in jails and prisons than in hospitals (Gilligan, 2001; Huxter, 2013; Lurigio, 2011; Markowitz, 2006). The combined stigma of SMI and incarceration leaves this population with unmet mental health needs and high rates of incarceration recidivism (Baillargeon, Binswanger, Penn, Williams, & Murray, 2009).…”
mentioning
confidence: 99%
“…Due to the large-scale closure of psychiatric hospitals, the federal war on drugs campaign, and communities with limited resources, the criminal justice system has become the default caregiver for a large number of persons with SMI, as there are now more people with SMI in jails and prisons than in hospitals (Gilligan, 2001; Huxter, 2013; Lurigio, 2011; Markowitz, 2006). The combined stigma of SMI and incarceration leaves this population with unmet mental health needs and high rates of incarceration recidivism (Baillargeon, Binswanger, Penn, Williams, & Murray, 2009).…”
mentioning
confidence: 99%
“…For the last two decades the population of mentally ill accused in the Canadian criminal justice system has been growing at a staggering rate of more than 10 percent per year (Schneider, 2000(Schneider, , 2010Schneider, Bloom, & Heerema, 2007). In fact, research from North America has reported that the number of persons with mental illness in jails and prisons is greater than the number of mentally ill individuals being treated in the community, making correctional facilities the largest de facto institution for the mentally ill population (Cosden, Ellens, Schnell, Yasmeen, & Wolfe, 2003;Gilligan, 2001;Ryan, Brown, & Watanabe-Galloway, 2010).…”
Section: Table Of Contentsmentioning
confidence: 99%
“…For the last two decades, the population of mentally ill accused in the Canadian criminal justice system has been growing at a staggering rate of more than 10% per year (Schneider, 2000(Schneider, , 2010Schneider, Bloom, & Heerema, 2007). Research from North America has reported that the number of persons with mental illness in jails and prisons is greater than the number of mentally ill individuals being treated in the community, making correctional facilities the largest de facto institution for the mentally ill population (Cosden, Ellens, Schnell, Yasmeen, & Wolfe, 2003;Gilligan, 2001;Ryan, Brown, & Watanabe-Galloway, 2010). Frequently suggested explanations for this growth include the perception that community-based mental health services are ill equipped to deal with offender populations (Lamb, Weinberger, & Gross, 2004), the implementation of tougher punishments for substance-related and quality of life offences (Lurigio & Harris, 2007), and the misconception that claiming ''not criminally responsible'' is a ''get-out-of-jail free'' card for the criminally accused (Schneider et al, 2007, p. 23).…”
Section: Introductionmentioning
confidence: 99%
“…Prisons as the new asylums. Gilligan (2001) postulated that centuries ago the mentally ill were most often housed in prisons and did not receive mental health services. In the mid 1800s, largely due to the work of Dorothea Dix, treatment of mentally ill changed profoundly.…”
Section: Mental Illness In Correctional Settingsmentioning
confidence: 99%
“…As the asylums became neglected warehouses, the movement of deinstitutionalization began with the Community Mental Health Act in the 1960s. According to Gilligan (2001), the purpose of this reform was to remove the mentally ill from destitute and isolated mental hospitals and provide them with community-based treatment. This, it was believed, would provide effective and affordable care without removing the patients from their community.…”
Section: Mental Illness In Correctional Settingsmentioning
confidence: 99%